(untitled) (Biological Sciences - PJSIR, 2000)
Grafting of acrylonitrile (AN) onto rice starch was accomplished using eerie ammonium nitrate (CAN) as catalyst. The effect of monomer, backbone, catalyst concentration on rate of conversion of monomer (Rp), rate of graft copolymcriza- tion (Rg), grafting effeciency (GE), grafting ratio (GR) is discussed. The absorption of water obtained from different sources by saponified product or gran copolymer was determined. The increment in absorbancy (g I-Ip g.l) is due to the formation or carboxyl anions (-COOo) in the polymer network which develops strong electrostatic forces. The effect of aqueous sodium chloride on saponified product is also discussed.